VALIDITAS RIWAYAT TAFSIR ABDULLAH IBN ABBAS PADA KITAB TAFSIR AL-QUR’ĀN AL-‘ADHĪM KARYA IBN KATSIR - Nurmayanti, Lutfiya; Abdul Kholid (Jurnal Studi Qur'an dan Tafsir, 2025)
In the tradition of classical exegesis, riwayat (narrations) hold a significant role in Qur'anic interpretation, providing profound explanations of the meanings contained within it. Narrations from the era of the Companions, in particular, are considered close to the truth, as they lived during the time of the Qur'an’s revelation. However, although narrations are deemed important, not all can be accepted uncritically; a thorough analysis is required to assess their authenticity. This study aims to examine the validity of the narrations attributed to Abdullah Ibn Abbas in the Tafsir Al-Qur’ān Al-‘Adhīm by Ibn Kathir. The research employs a descriptive-analytical method, analyzing the narrations found in Ibn Kathir's exegesis through nine transmission chains from Ibn Abbas, ranging from the most authentic to the weak ones. The findings reveal that Ibn Kathir was selective in including authentic narrations from Ibn Abbas, yet some weak narrations were still identified. These results highlight the necessity of exercising caution when using narrations as sources of exegesis, even those attributed to Ibn Abbas.